Positive Effects of Illness following Acute Myocardial Infarction - Afrasiabifar A. PhD; Hassani P PhD; Fallahi Khoshknab M. PhD; Yaghmaei F. PhD (Iran University of Medical Sciences, 2011)
Background & Aim: Myocardial infarction is an important event and a huge change in patients' and their family life. The negative psychosocial consequences of the disease are well documented. However, studies on positive effects following myocardial infarction are much more limited. The aim of this study was to explore positive effects of illness following acute myocardial infarction.   Material & Methods: This paper is a part of findings of a more extensive grounded theory study. Eighteen people with first time myocardial infarction were selected by purposeful and theoretical sampling. Semi-structured interviews were used for data collection. The data were analyzed using constant comparison method   Results: The findings showed that the participants have experienced one or more positive effects of the disease. Positive effects of illness were emerged in three main categories including: healthy lifestyle, worthwhile life/health, and promotion of social interaction/ interpersonal relationship.   Conclusion: Patient with myocardial infarction experience huge tensions. However, the disease would also result in positive effects which could, in turn, facilitate recovery from illness and the process of adjustment to illness.